2015
DOI: 10.1007/s12298-015-0291-5
|View full text |Cite
|
Sign up to set email alerts
|

Biological seed priming mitigates the effects of water stress in sunflower seedlings

Abstract: The sunflower (Helianthus annuus L. cv. PAC 36) seedlings were inoculated with plant growth promoting rhizobacteria (PGPR), viz. Azotobacter chroococcum (A+), Bacillus polymyxa (B+), separately and in combination of the two (AB+). Relative water content and seedling growth were maximum in AB+ seedlings under control. Water stress significantly decreased the RWC, growth and dry mass of non-inoculated seedlings. However, inoculated seedlings maintained higher growth even under water stress. Pigments and protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 40 publications
(33 reference statements)
3
12
0
Order By: Relevance
“…The photosynthetic pigments were accumulated in sunflower seedlings, and seeds were inoculated with plant growth promoting rhizobacteria under water stress (Singh et al, 2015). Similar results of pigment accumulation were obtained in our research.…”
Section: Discussionsupporting
confidence: 88%
“…The photosynthetic pigments were accumulated in sunflower seedlings, and seeds were inoculated with plant growth promoting rhizobacteria under water stress (Singh et al, 2015). Similar results of pigment accumulation were obtained in our research.…”
Section: Discussionsupporting
confidence: 88%
“…In this work, callus growth was not significantly different plus or minus 10% PEG over a period of 6 months, suggesting that calli on PEG acquired tolerance to osmotic (water) stress ( Figure 1 ) probably mediated by an early osmotic adjustment which was likely associated to various modifications at the cellular level ( Singh et al, 2015 ). In fact, both cell viability and mitotic index were higher in the PEG treated cells compared to the control indicating a healthy and proliferating culture.…”
Section: Discussionmentioning
confidence: 60%
“…which was correlated with endoreduplication during fruit development. Our results do not seem to indicate that there has been irreversible DNA damage due to the osmotic stress imposed on callus, and it would therefore be legitimate to link this to WEE1 expression and its role in replication checkpoint and DNA damage and the possibility that the PEG concentration used and the long-term culture on it resulted in priming ( Singh et al, 2015 ). Other genes could also be involved in the process though, and, in this respect, in order to protect their gene integrity from DNA damage plants are capable of activating a specific response system that regulates the cell cycle, but also DNA repair and programmed cell death where genes such as Suppressor Of Gamma response 1 ( SOG1 ) ( Yoshiyama et al, 2014 ) and Breast Cancer 1 ( BRCA1 ) ( Block-Schmidt et al, 2011 ) are known to play a central role in DNA repair, chromosome segregation and chromatin remodeling So the increase in MtWEE1 seen here may be both linked to the increase in endoreduplication and required to protect the cells from DNA damage induced by the PEG-induced osmotic stress treatment.…”
Section: Discussionmentioning
confidence: 63%
“…Nitrogen assimilation occurs in plants via two key enzymes, glutamine synthetase (GS) and glutamate synthase (GOGAT). Singh et al [70] showed that soil drying decreased the activities of these enzymes together with a decrease in N absorption and content of nitrogenous compounds in leaves of sunflower seedlings. Our results show that the abundance of GS and GOGAT decreased in the two commercial genotypes under stress, but no change was observed in the abundance of these two enzymes in the S10 genotype.…”
Section: Discussionmentioning
confidence: 99%